A utilização da contabilidade e sua relação com a procedência dos autos de infração da Secretaria da Fazenda do Estado do Ceará - Moura, Lara Pinheiro de (2013)
The utilization of accounting elements in tax evasion reports gave rise to frequent discussions within state tax agencies. This research assumes that tax evasion reports that are based on accounting elements have precedence over the ones which are not, since with a detailed accounting of administrative data, there is more control over monetary or material modifications which occurred within a company’s assets. This research examined the utilization of accounting in 127 tax evasion reports issued by SEFAZ-CE and brought to a second hearing in the last two months of 2012, with relation to precedence, aiming at qualitatively describing the cases referring to tax evasion reports from this sample. After raising and examining the data, it was verified that the most common reasons to qualify a report as lax were omissions and lack of proper recording of entries and exits; and it was verified that with other types of reports this happens less frequently. With regard to auditing, it was verified that there was a high incident of audited reports, over 50%. It was also confirmed that, within the reports that utilized accounting elements, the number of audited reports was a little smaller than the reports that didn’t utilize them. With respect to the identification of accounting elements present in the fiscal data of the tax evasion reports, it was verified that the most recurrent ones were Accounting Demonstrations and Accounting Results. With regard to measuring the incidence of precedence in the tax reports that were based on accounting elements compared to the ones that were not, it was verified an incidence of 83% and 86%, respectively; which demonstrates a similar precedence incidence between the two. Moreover, it was concluded that currently SEFAZ-CE auditors have more confidence and knowledge when applying auditing methods that are based only on fiscal elements; since they represent 76% of the sample, against 24% of reports that utilized accounting elements. Lastly, it was verified that the main reasons for tax reports to be judged inadmissible were when the reasons for the auditing report were discredited; and the attestation, through investigation, that the evasion did not occur.